New scenario for speciation in the benthic dinoflagellate genus Coolia (Dinophyceae) - Leaw, Chui-Pin; Tan, Toh Hii; Lim, Hong Chang; Teng, Sing Tung; Yong, Hwa Lin; Smith, F. Kirsty; Rhodes, Leslie; Wolf, Matthias; Holland, William C.; Vandersea, Mark W.; Litaker, Wayne; Tester, Patricia A.; et al. (Elsevier Ltd., 2016)
In this study, inter- and intraspecific genetic diversity within the marine harmful dinoflagellate genus Coolia Meunier was evaluated using isolates obtained from the tropics to subtropics in both Pacific and Atlantic Ocean basins. The aim was to assess the phylogeographic history of the genus and to clarify the validity of established species including Coolia malayensis. Phylogenetic analysis of the D1-D2 LSU rDNA sequences identified six major lineages (L1–L6) corresponding to the morphospecies Coolia malayensis (L1), C. monotis (L2), C. santacroce (L3), C. palmyrensis (L4), C. tropicalis (L5), and C. canariensis (L6). A median joining network (MJN) of C. malayensis ITS2 rDNA sequences revealed a total of 16 haplotypes; however, no spatial genetic differentiation among populations was observed. These MJN results in conjunction with CBC analysis, rDNA phylogenies and geographical distribution analyses confirm C. malayensis as a distinct species which is globally distributed in the tropical to warm-temperate regions. A molecular clock analysis using ITS2 rDNA revealed the evolutionary history of Coolia dated back to the Mesozoic, and supports the hypothesis that historical vicariant events in the early Cenozoic drove the allopatric differentiation of C. malayensis and C. monotis.